Who was Harry Houdini? - Sutherland, Tui T.; O'Brien, John 1953- (New York, NY : Grosset & Dunlap, 2002)
A biography of the famous magician who was also a movie star and a pioneer pilot.
So you want to be an American -- So you want to be a magician -- So you want to be famous -- So you want to be a star! -- So you want to be amazing -- So you want to be a pilot -- So you want to be a movie star! -- So you want to be an illusionist -- So you want to be a hero -- So you want to be a detective -- So you want to be remembered forever.
Keywords: Houdini, Harry, -- 1874-1926 -- Juvenile literature; Houdini, Harry, -- 1874-1926; Magicians -- Biography -- United States; Escape artists -- Biography -- United States; Magicians